Operational and structural diagnosis of sewerage and drainage networks in Côte d’Ivoire, West Africa - Ouattara, Z. A.; Kabo-Bah, A. T.; Dongo, K.; Akpoti, Komlavi; Siabi, E. K.; Kablan, M. K. A.; Kangah, K. M. (Frontiers Media, 2023)
In Cote d’Ivoire, the failure of urban sewage systems is a crucial problem for the drainage of wastewater and rainwater. This failure is due to many factors and therefore, calls for diagnostic studies. The present study aimed at analyzing these networks in order to identify the dierent factors that contribute to the operational and structural degradation in selected sewerage and drainage networks in Abidjan, Cote d’Ivoire. The method used in the study involved semi-structured interviews, video camera inspection and socio-environmental field surveys (geographical survey and household survey), followed by descriptive statistics. The results revealed that many structural, environmental and behavioral practice contribute to the progressive degradation of urban sewage systems. These factors are essentially those that prevent the normal flow of wastewater in the pipes such as the illegal dumping of solid waste, the unauthorized connection of wastewater networks, unsustainable urban agricultural practices, as well as the high concentration of vegetation on both sides of the network and the dilapidated infrastructure of the wastewater and rainwater networks. It was found that these factors are at the origin of the clogging and degradation of the sewers since 85% of the residents used these sewers as a dumping ground for solid waste.